Disability, Right Monitoring, and Social Change: Building Power Out of Evidence - Haley, Tobin LeBlanc (Canadian Review of Social Policy / Revue canadienne de politique sociale, 2017)
Book Review of Disability, Right Monitoring, and Social Change: Building Power Out of Evidence (2015) Edited by Marcia H. Rioux, Paula C. Pinto and Gillian Parekh. Toronto: Canadian Scholars' Press.